The effect of a prolonged period of endurance training at moderate altitude on VO2max - Heinicke, I.; Cajigal, J.; Rawlings, P.; Behn, C.; Gassmann, M.; Heinicke, K. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Altitude training is a frequently used method for endurance athletes to improve exercise performance at altitude and sea level. In moderate acute hypoxia maximal O2 consumption (VO2max) is reduced proportional to the elevation and increases upon acclimatisation. However, after a shorter period of 2-4 weeks at altitude VO2max remained still reduced compared to sea level values. The purpose of this study was to test the hypothesis that acclimatization plus training at moderate altitude (2800 m) for a prolonged period (6 weeks) leads to a complete recovery of endurance performance at altitude and improved performance at sea level. Methods: Nine endurance trained athletes (3 females, 6 males) were investigated during a 6 week training camp at moderate altitude of 2800 m in Portillo, Chile. The moderate-conditioned athletes are members of the development program in biathlon sport in Chile and have been started intensively training for 4 years. The daily training time of the athletes (mean age [SD], 24.9 ± 1.2 years) was approximately 4-6 hours with one day per week rest. To determine endurance performance athletes performed a VO2max test by using a cycle ergometer at sea level before and 3 days after altitude training as well as on day 2 and 42 at altitude. Preceded by a five minute warm-up period at 100 watts, the workload was increased until subjective exhaustion by steps of 17, 17, and 16 Watts every minute, i.e. by 50 Watts within three minutes. To assess hematological changes and erythropoietic activity we determined hemoglobin ([Hb]), hematocrit (Hct), plasma erythropoietin (Epo) and soluble transferrin receptor (TfR) levels as well as the iron status at sea level, on day 2 and every 10 days at altitude. Results: VO2max (ml/kg*min) was significantly reduced by 12% (50.1±3.9 to 44.4±4.0) upon arrival at altitude and reached sea level values after 42 days at altitude (50.0±5.3). Sea level performance after the altitude training camp was significantly improved by 11% (55.4±5.9). The same pattern was found for the maximal aerobic power (MPA). At altitude mean MPA decreased 10% below pre-altitude value (309±43 to 278±37 W), reached nearly sea level values after 42 days altitude training (302±48) and was post-altitude increased by 14% (351±35). [Hb] (14.7±1.3 to 16.5±1.1 g/dl) and Hct (45.0±3.1 to 48.8±2.4 %) were significantly increased at the end of the altitude training period compared to sea-level values. Plasma Epo significantly increased on day 2 and 12 at altitude (6.9±1.6 to 14.8±5.1, 11.0±4.1 mU/ml) compared to sea level values and thereafter significantly decreased during the stay at altitude. TfR was significantly elevated in average by 17% after 12 until 42 days at altitude. Ferritin showed lower values during the training camp, serum iron and transferrin remained within the normal range. Discussion/Conclusion: Whether an exercise training regimen is successful in improving exercise performance at altitude and sea level depends on various factors like conditioning level, training stimuli, elevation and degree of acclimatization. Our athletes showed increased [Hb] and Hct levels during the altitude training improving oxygen transport capacity. The observed elevated Epo levels at the beginning of the altitude training, the elevated TfR level and the decreased ferritin level indicated enhanced erythropoietic activity. As expected, acute moderate hypoxia provoke a decrease in VO2max. The moderate-conditioned athletes reached pre-altitude performance level at altitude and increased performance at sea level. Based on our data we propose that 6 week of altitude training at 2800 m is sufficient to be optimal prepared for a competition at the given altitude as well as to improve sea level performance. However, we can not distinguish between whether the increased performance was due to hypoxic stress, the training effect or a synergistic effect of both. The main finding of this study is that acclimatization plus training at moderate altitude for 6 weeks results in a complete recovery of endurance performance at altitude and improved performance at sea level in moderate-conditioned athletes.